Newcomers from the other side of the globe: International students' local information seeking during adjustment. Issue 1 (27th December 2016) - Oh, Chi Young; Butler, Brian S.
ABSTRACT: Through the findings from a longitudinal survey and the preliminary analysis of the follow‐up interviews, this paper explores how international newcomer students' needs for local information and their information‐seeking behavior develop during adjustment to new host environments. Also, this study examines the relationships between their local information behaviors and the demographic and socio‐national contexts of newcomer students. The results are discussed in a way to deepen our understanding of international students' information‐seeking behavior during adjustment to unfamiliar local environments and the various contexts that shape the changes of their information behavior over time. Finally, this paper provides implications for developing information behavior models and theories in the contexts of newcomers and for designing information systems, policies, and services to better support international students' information practices and adjustment in unfamiliar environments.